The Effectiveness of Using the Lecture Method at SMK Negeri 1 Parepare - Muhammad Iqram Ikhsan; Risma Niswaty; Sirajudddin Saleh; Sitti Hardiyanti Arhas (Universitas Negeri Makassar, 2019)
This study aims to determine the effectiveness of the use of lecture methods in class X introductory subjects administrative office administration department SMK Negeri 1 Parepare. This research uses a type with qualitative descriptive approach. Informants in this study as many as five people. Data collection is done through interview technique, observation, and documentation. The results showed that. Teachers have applied the learning process such as, doing the preparation stage of learning well, performing the implementation phase starting from the opening step until the presentation step has been done optimally, and the last to do the ending stage by giving opportunity to the students to conclude the material taught and doing evaluation to students has been done quite effectively. So the use of lecture methods in class X introductory subjects administrative office administration department of SMK Negeri 1 Parepare run effectively.